The role of proximal circumstances and child behaviour in toddlers' risk for minor unintentional injuries. Issue 1 (17th June 2014) - Kuhn, Jennifer; Damashek, Amy
Abstract : Background: Much of the research on child injury risk has focused on trait-like factors (eg, hyperactivity, child gender) that influence injury risk rather than state-like factors (eg, environmental circumstances, child behaviour). Additional research is needed to better identify the proximal risk factors for children's risk for unintentional injury. Objectives: The present study examined the antecedents to minor unintentional injury events and whether unusual circumstances and child behaviour predicted injury risk. Methods: The study used archival data that were collected via biweekly in-person interviews with 170 mothers of toddlers (15–36 months) for 6 months. A case crossover design was used to predict children's risk for injury from proximal risk factors. Results: Children were at a higher risk for injury when circumstances were unusual and when they were engaging in an unusual behaviour. When a child was engaging in an unusual behaviour, higher levels of maternal supervision predicted lower injury risk. Children were more likely to be injured in a new environment, in an environment with animals or other people, in an environment with hazards or when engaging in a new activity or in a familiar activity performed in an unfamiliar way. Conclusions: The results indicate that toddlers may be at a greater risk for minor unintentional injury when environmental circumstances are outside of the norm or when a child is engaging in unusual behaviours. The findings also indicate that higher levels of caregiver supervision may be especially beneficial when children are engaging in new or unfamiliar activities.